1,4-Dipolar cycloaddition in organic synthesis: a facile route to isoquinoline fused heterocycles - Nair, Vijay; Sreekanth, Anakkalil R.; Abhilash, N.; Biju, Akkattu T.; Varma, Luxmi; Viji, Sreemathi; Mathew, Saumini (Arkivoc, 2005)
The three component condensation reactions involving isoquinoline, dimethyl acetylenedicarboxylate and carbonyl dipolarophiles such as o- and p-benzoquinones and Nsubstituted isatins constitute a one-pot synthesis of a variety of [1,3]oxazino isoquinoline derivatives via 1,4-dipolar cycloaddition.